2002
DOI: 10.1086/342711
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofRhododendron maximumThickets on Tree Seed Dispersal, Seedling Morphology, and Survivorship

Abstract: In the southern Appalachian forests, the regeneration of canopy trees is severely inhibited by Rhododendron maximum L., an evergreen understory shrub producing dense thickets. While light availability is a major cause, other factors may also contribute to the absence of tree seedlings under R. maximum. We examined the effects of R. maximum on several life history stages of tree species, including seed dispersal, seed bank germination, seedling growth, and survivorship. We found no significant effect of JR. max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 54 publications
3
48
1
Order By: Relevance
“…Therefore, it is clear that seedlings of both species had a greater chance of experiencing irradiance near or below the light compensation point for photosynthesis in F + R sites than in F sites. Consistent with the observed carbon gain at these light levels, mortality of P. serotina seedlings in Coweeta ( > 90%) was much greater than Q. rubra (50%, Lei et al 2002) over 2 years. While our findings of the greater shade tolerance of Q. rubra over P. serotina agree with Farrar (1995), Canham et al (1994) found higher sapling mortality over 5 years in Q. rubra (81%) than P. serotina (31 %).…”
Section: Availability Of Dzfluse Lightsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, it is clear that seedlings of both species had a greater chance of experiencing irradiance near or below the light compensation point for photosynthesis in F + R sites than in F sites. Consistent with the observed carbon gain at these light levels, mortality of P. serotina seedlings in Coweeta ( > 90%) was much greater than Q. rubra (50%, Lei et al 2002) over 2 years. While our findings of the greater shade tolerance of Q. rubra over P. serotina agree with Farrar (1995), Canham et al (1994) found higher sapling mortality over 5 years in Q. rubra (81%) than P. serotina (31 %).…”
Section: Availability Of Dzfluse Lightsupporting
confidence: 81%
“…Three, tree seedlings were unable to achieve increased shade acclimation under the dimmer R. maximum cover, resulting in greater carbon deficit. Our data showed that most tree seedlings will not persist for more than 2-3 years in the shade of the thickets (Lei et al 2002 Seedlings in these brighter F + R locations should persist for longer periods of time. However, the absence of older tree seedlings in these brighter patches under R. maximum thickets implicates other contributing factors, such as below-ground competition and interference with mycorrhizal association Nilsen et al 2001), are further restricting tree seedling survival under the thickets.…”
Section: Discussionmentioning
confidence: 68%
“…Shrub understories decrease seedling density, growth and survival (Beckage et al, 2000;Nilsen et al, 2001;Collier et al, 2002;Lei et al, 2002;Fagan and Peart, 2003;Gorchov and Trisel, 2003;Lambers and Clark, 2003). This effect has been found with invasive shrubs outside their native range, such as Lonicera maackii and Rhamnus frangula, as well as shrubs in their native range such as Rhododendron maximum, Buxus sempervirens and Juniperus communis.…”
Section: Introductionmentioning
confidence: 92%
“…Shrub canopies limit resources required for seedling establishment and survival. Shrubs reduce light levels on the forest floor (Beckage et al, 2000;Nilsen et al, 2001;Lei et al, 2002) and decrease soil moisture and nutrient levels (Putz and Canham, 1992;Nilsen et al, 2001). Litter accumulation (Beckage et al, 2000) and increased seedling predation by small mammals under shrubs (Rousset and Lepart, 2000) also create difficulties for seedling establishment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation